Bone health and fracture risk factors in children living in New Zealand : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Nutritional Science at Massey University, Albany, New Zealand - Delshad Siyahkaly, Maryam (Massey University, 2021)
Background: Fractures are common in childhood but are a neglected public health issue. A complex interplay of non-modifiable (e.g. genetics) and modifiable risk factors (e.g. obesity, physical activity, calcium intake, sugar-sweetened beverages (SSB), and vitamin D status) have been associated with childhood fractures. Early identification of risk factors during childhood could enable lifestyle changes to be instigated, thus enhancing bone mineralisation, preventing fractures, and improving adult bone health. Vitamin D is an essential nutrient for the absorption of calcium from the intestine, regulation of serum calcium, and bone health. An adequate 25(OH)D concentration is considered important for ensuring bone health during childhood since there is a relationship between vitamin D deficiency and insufficiency and skeletal health problems such as rickets, metabolic bone disease, and hypocalcaemia during childhood. Unfortunately, there is limited data available regarding the vitamin D status and risk factors for vitamin D deficiency in New Zealand children. Measuring paediatric bone mineral status can help us to find children who could be exposed to an increased risk of bone problems (e.g. osteopenia, osteoporosis) later in their life. Quantitative ultrasound (QUS) is a measuring method commonly employed in paediatric populations for assessing skeletal status. Childhood overweight and obesity are also associated with developing musculoskeletal problems, injuries, and fractures early in childhood. Recently, bioelectrical impedance analysis (BIA) has received much attention as a method for measuring body composition. However, the validity of these two devices needs to be investigated in a New Zealand paediatric population. Aims: The main aim of this study is to explore fracture history and related risk factors in children living in Auckland, New Zealand. The secondary aims are to determine the wintertime vitamin D status of children living in Auckland and its determinants and to validate the QUS and in-built algorithm of BIA measurements against dual-energy X-ray absorptiometry (DXA) in children. Methods: This was an observational, cross-sectional study in a sample of school-age children (aged 8 – 13 years old) living in Auckland (during August 2016 and 2017 – late winter in the southern hemisphere). Six local primary schools across Auckland were selected. We originally approached schools through a collaboration of primary school science teachers and asked for expressions of interest. We then endeavoured to recruit schools specifically to include a wide range of socio-demographic levels and ethnicities. All school children within the specified age group were invited to participate. Children were stratified by gender (2 groups), ethnicity (6 categories), and skin colour (4 groups), and logistic regression used to determine the contribution of risk factors for fracture and vitamin D deficiency. A sample of 10-15 per factor per group is the standard requirement for regression analysis, meaning that 480-720 participants would be required to investigate the above-mentioned factors. To validate the QUS and BIA, a sample of 128 children was calculated based on the G*Power program [version 3.1 software: medium effect size: 0.6; power: 95%; the level of significance: 5%]. Healthy children were recruited from primary schools. Children were excluded if they had 1) a history of any disease affecting vitamin D metabolism (e.g. cardiac, kidney or liver disease) or 2) a history of any long-term medication use (e.g. steroids) 3) had any surgical implants, metal screws or similar, or 4) had a cast. Children received an envelope containing a study information sheet, consent form, and some questionnaires (e.g. fracture history, siblings’ history of fractures, family osteoporosis history, physical activity (PA), ethnicity, skin colour, and sun exposure). A dairy and other calcium-containing foods food frequency questionnaire and SSB questionnaire were completed by the children with help from parents. Children who, together with their parents, gave written consent and returned the completed questionnaires, were measured at school. Tests included anthropometric (weight and height) and body composition (bioelectrical impedance analysis, InBody720, Seoul, Korea) measurements, and finger-prick blood spot to measure capillary 25-hydroxyvitamin D (25(OH)D) concentrations. Some children were invited to the Nutrition Research Facility at Massey University, Albany on one occasion to test the validity of the QUS and BIA measurements against a DXA scan. Total body less head (TBLH), bone mineral content (BMC), bone mineral density (BMD), and body composition (fat-free mass, fat mass, and body fat percentage (%BF)) were measured with DXA (QDR Discovery A, Hologic, USA); calcaneal BMD and stiffness index (SI) with QUS (Sahara QUS, Hologic, USA), and total mass and %BF on the InBody 230 (Biospace Ltd., Seoul, Korea). Relative validity was assessed using Pearson’s and Lin’s concordance correlation coefficients (CCC), and Bland-Altman plots. Results: A total of 647 children (354 girls) with the mean ± standard deviation (SD) age of 9.8 ± 0.7 years were recruited. New Zealand European (n = 252) (NZE) and South Asian (n = 68) children reported the lowest (20.2%) and highest (44.1%) fracture incidence, respectively. New Zealand European, compared to South Asian children, had higher 25(OH)D concentrations (74.6 ± 19.8 vs. 48.4 ± 19.3 nmol/L, P < 0.001), higher total calcium intake (764.0 ± 394.4 vs. 592.7 ± 266.3 mg/day, P < 0.018), and lower %BF (19.5 ± 6.6 vs. 23.4 ± 8.4, P < 0.003). The main determinants of fracture history for boys were high %BF, low 25(OH)D, low calcium intake, high SSB consumption, siblings’ fracture history, family osteoporosis history, and being South Asian; and for girls were high SSB consumption, siblings’ fracture history, and family osteoporosis history. Five hundred and seven children agreed to do the finger prick test. Mean ± SD 25(OH)D concentration were 64.0 ± 20.8 nmol/L, with 30.8% of the population presenting with 25(OH)D ≥ 75 nmol/L, 41.4% 50-75 nmol/L, and 27.8% < 50 nmol/L. Capillary 25(OH)D was significantly higher in NZE compared to all other ethnic groups (75.0 ± 20.1 nmol/L, P < 0.001). Children with dark/brown skin colour had lower 25(OH)D concentration compared to other categories of skin colour (51.7 ± 18.0 nmol/L, P < 0.001). Using multiple logistic regression analysis, determinants of 25(OH)D were %BF and ethnicity. In 124 healthy children, positive correlations between QUS SI and DXA (BMC and BMD) were observed (range = 0.30-0.45, P < 0.01). Results from Lin’s CCC test showed that almost perfect correlations between BIA and DXA fat-free mass (0.96), fat mass (0.92), and substantial correlation for %BF (0.75) (P < 0.05). Conclusion: Approximately one-quarter of our participants reported one or more fractures during their childhood. Our results showed that being of South Asian ethnicity was a significant risk factor for fracture in boys. Some children were at high risk of vitamin D deficiency during winter months, for whom vitamin D supplementation might be recommended. Good nutrition (especially good sources of calcium and reducing SSB intakes) should be recommended to children during growth and development to reduce their risk of fractures. Among 507 children, approximately one-third had 25(OH)D < 50 nmol/L. Determinants of a 25(OH)D < 50 nmol/L included %BF and ethnicity. Wintertime serum 25(OH)D was highly variable. There are some children at high-risk of 25(OH)D < 50 nmol/L for whom supplementation may be considered. The current study was the first to evaluate the validity of calcaneal QUS and BIA against DXA in a paediatric New Zealand population for measuring bone density and body composition, respectively. Although BIA results were not as accurate as DXA and DXA remains the gold standard method for clinical assessment, BIA can be an alternative method for investigating body composition among children in large cohort field studies. Calcaneal QUS and DXA are not interchangeable methods for measuring bone density in children similar to our study population.
Keywords: Fractures in children; Risk factors; Osteoporosis in children; New Zealand; Auckland; Vitamin D deficiency; bone; fracture; children; determinants; milk consumption; sugar-sweetened beverages; physical activity; obesity; vitamin D; 321005 Public health nutrition